Describing symptoms using the Symptom Screening in Pediatrics Tool in hospitalized children with cancer and hematopoietic stem cell transplant recipients. (23rd March 2018) - Johnston, Donna L.; Hyslop, Shannon; Tomlinson, Deborah; Baggott, Christina; Gibson, Paul; Orsey, Andrea; Dix, David; Price, Vicky; Vanan, Magimairajan; Portwine, Carol; Kuczynski, Susan; Spiegler, Brenda; et al.
Abstract: Objectives were to describe any bothersome symptom and severely bothersome symptoms in inpatient children with cancer and hematopoietic stem cell transplant (HSCT) recipients. We included children 8–18 years of age with cancer or HSCT recipients who were receiving active treatment for cancer, admitted to hospital, and expected to be in hospital 3 days later. We administered the self‐report Symptom Screening in Pediatrics Tool (SSPedi). We described those who identified any degree of symptom bother (at least "a little") and those who rated the degree of bother as severe ("a lot" or "extremely"). Factors associated with severe symptoms and total SSPedi scores were examined using multiple logistic and linear regression. Among the 302 patients, 298 (98.7%) reported having any bothersome symptom and 181 (59.9%) had at least one severely bothersome symptom. In multiple regression, older children were significantly more likely to have at least one severely bothersome symptom (15–18 and 11–14 years vs. 8–10 years; P  = 0.008) and to have higher total SSPedi scores ( P  = 0.0003). Those with relapsed disease were more likely to have at least one severely bothersome symptom (odds ratio 2.1, 95% confidence interval 1.1–4.3; P  = 0.037) and HSCT recipients were more likely to have higher symptom scores ( β  = 3.48, standard error = 1.6; P  = 0.030). Almost all children receiving cancer therapies experience bothersome symptoms and 60% have at least one severely bothersome symptom. Older children experienced more severely bothersome symptoms and higher symptom scores. Future studies should follow children longitudinally to better understand the symptom trajectory and should institute interventions to manage symptoms. Abstract : Objectives were to describe any symptom and severely bothersome symptoms in inpatient children with cancer and hematopoietic stem cell transplant (HSCT) recipients. Almost all children receiving cancer therapies experience bothersome symptoms and 60% have at least one severely bothersome symptom. Older children were more likely to have severely bothersome symptoms and to have higher symptom scores.